2018
DOI: 10.15294/biosaintifika.v10i1.11870
|View full text |Cite
|
Sign up to set email alerts
|

Mahameru Soybean (Glycine max) Cultivar, High Salinity Tolerant

Abstract: Mahameru cultivar is high salinity tolerant cultivar. The previous study result showed Mahameru cultivar could tolerate 140 mM NaCl, but Cilacap Coast salinity levels often reaching 200 mM NaCl. A research of salinity stress on Mahameru cultivar at 200 mM NaCl have not conducted yet. Therefore to conduct the research of Mahameru at high salinity stress to obtained high salinity tolerant soybean cultivar. The observed variables are anatomy (epidermis thickness, the density of stomata and trichomes, palisade thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…The density of trichomes on the abaxial part of soybean cultivar "Mahameru" leaves in the control treatment (1.80/mm 2 ) was lower than the 200 mM NaCl concentration (2.80/mm 2 ). In comparison, the adaxial part of the control treatment of Mahameru soybean leaves showed a lower of density trichomes (2.40/mm 2 ) than the 200 mM NaCl concentration (2.60/mm 2 ) [24].…”
Section: Discussionmentioning
confidence: 75%
“…The density of trichomes on the abaxial part of soybean cultivar "Mahameru" leaves in the control treatment (1.80/mm 2 ) was lower than the 200 mM NaCl concentration (2.80/mm 2 ). In comparison, the adaxial part of the control treatment of Mahameru soybean leaves showed a lower of density trichomes (2.40/mm 2 ) than the 200 mM NaCl concentration (2.60/mm 2 ) [24].…”
Section: Discussionmentioning
confidence: 75%
“…Then the lower epidermal tissue is significantly thicker on the leaf base. According to Juwarno et al (2018) Increased thickness of the lower epidermis related to prevention of water loss.…”
Section: Anatomical Thickness Analysis Of Leaves Of Six Types Of Mono...mentioning
confidence: 99%
“…According to Singh et al (2008), peanut genotypes with high susceptibility to saline conditions show toxicity symptoms at the beginning of their growth and earlier mortality, while tolerant genotypes persisted. Juwarno et al (2018) reported that tolerant cultivar had tendency of increasing chlorophyll content as salinity increase, therefore it could maintain the green leaves.…”
Section: Salt Toxicity Scoresmentioning
confidence: 99%